(untitled) (Jurnal Manajemen Bisnis, 2026)
This study examines the role of social media marketing in influencing customer engagement, trust, and customer loyalty among local bakery customers in Bogor City. The research aims to analyze the direct effects of social media marketing on engagement, trust, and loyalty. A quantitative approach was employed using Structural Equation Modeling (SEM) with data collected through questionnaires. The results show that social media marketing has a significant effect on customer engagement and trust but does not directly influence customer loyalty. Customer engagement and trust also do not significantly affect loyalty. These findings imply that customer loyalty requires factors beyond digital interaction, particularly product quality and customer experience.